Maintaining Skill Development of Newly Qualified Physical Education Teachers: Mentorship After Graduation - Evans, Stuart (GILE Journal of Skills Development, 2024)
High percentages of newly qualified teachers drop out during their first 5 years of teaching in the classroom. Often, formal support systems are put in place to overcome ‘practice shock’. Yet this practice shock is generally associated with traditional academic subjects such as mathematics, humanities and science. The often-marginalised subject of physical education can be largely neglected when newly qualified teachers are considered. One strategy to reduce practice shock is that of an established mentoring program. The large volume of literature on mentoring across an array of education subjects suggests that mentoring is a valued skill. However, while mentoring is acknowledged as an essential prerequisite for successful teacher induction, its effectiveness in physical education may vary depending on the mentor’s quality of support and the mentee’s initial professional beliefs. This article draws on a structured analysis of research-based articles on mentoring for newly graduated physical education teachers and explores the discipline between mentee and mentor to make more valid inferences about the roles, responsibilities and outcomes of mentoring. The need for clarity around a physical education teacher’s role as a mentor and associated responsibilities relative to the provision of emotional support and guidance are examined along with suggestions for explicit transmission-oriented mentoring approaches to support beginning teachers’ professional development.